Correlation analysis between restructuring and employee’s loyalty in Petronas Dagangan Berhad (PDB) / Mohd Nazree Joblee and Fadhillah Arif Ghazi - Joblee, Mohd Nazree; Arif Ghazi, Fadhillah (Faculty of Business and Management, 2016)
Purpose – This research was conducted with the purpose of analyzing the correlations that exists between restructuring and employee loyalty. Restructuring is one of the accepted strategy done by an organization in order to react with the declining profit and increase in operational costs that usually caused by an unfavorable economic situation. Loyalty is the psychological state of an employee towards their feeling of attachment and commitment towards the organization and its improvement. Therefore, we want to prove that whether there is any relationship that occurs between restructuring and employee loyalty.